The Potential of Wind Energy in Malaysian Renewable Energy Policy: Case Study in Kudat, Sabah. Issue 5 (July 2014) - Ibrahim, M.Z.; Albani, A.
Recently, a study of wind energy potential at selected areas in Malaysia was completed by Universiti Malaysia Terengganu (UMT). One of selected sites is at Kudat, Sabah. The wind atlas analysis and application Program (WAsP) was used to investigate the wind energy potential by developing the regional wind diagram in the considered site at Kudat. Different types of data have been collected about climate, topography, obstacles and surface roughness of the land. The observed wind climates (OWC) of the wind mast had been created. The wind atlas and the resource grid have been calculated and analyzed, especially in the high wind resource areas and using criteria based on proximity, similarity and ruggedness index (RIX). The 22kW rated power wind turbine was selected due to it's best capacity factor. Then, the annual energy production of wind farms were evaluated by taking the turbine wake losses into account. The obtained results showed that the optimal place for single units of wind energy production is located in the farm zone 2 with a potential varying from 37.5–43.1 MWh per year. In economic aspect, the predicted FiT rates in between RM0.30 and RM1.30 were tested by using net present value (NPV) and payback period (PBP) approach. Finally, the conducive FiT rates for wind projects with secured investment were identified, and the rates were in between RM0.46 and RM0.80 per kWh.